Pengaruh future time perspective terhadap pengambilan keputusan pada mahasiswa - Sakinah Nur Rokhmah; Zakarija Achmat (Cognicia, 2022)
Students are often faced with many situations that involve the right decision-making process in various situations, such as when choosing courses in each semester, where to live, and activities during the holidays. The perspective of time is one part that is considered in the decision-making process. If someone thinks that they still have a long time, it could be that the individual will delay deciding to consider more things. This research is a quantitative correlational study to determine the effect of the future time perspective on decision making. The sample in this study was 117 students with a simple random sampling method. The instruments used to measure the two variables are the future time perspective survey and the Melbourne decision-making questionnaire, adapted into Indonesian. The data were analyzed using simple linear regression analysis using SPSS 25. This study proves that there is an effect of future time perspective on decision making with a predictor contribution of 17%. Keywords: Decision making, future time perspective, student